2017
DOI: 10.1111/asj.12824
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α‐ketoglutarate supplementation improves hepatic and intestinal energy status and anti‐oxidative capacity of Cherry Valley ducks

Abstract: α-Ketoglutarate (AKG) is an extensively used dietary supplement in human and animal nutrition. The aim of the present study was to investigate effects of dietary AKG supplementation on the energy status and anti-oxidative capacity in liver and intestinal mucosa of Cherry Valley ducks. A total of 80 1-day-old ducks were randomly assigned into four groups, in which ducks were fed basal diets supplemented with 0% (control), 0.5%, 1.0% and 1.5% AKG, respectively. Graded doses of AKG supplementation linearly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…AKG is an important intermediate in the TCA cycle, impacts ATP production as a key point in the anaplerotic pathway [ 7 , 15 , 46 , 47 ], involved in the biosynthesis of proteins and amino acids [ 48 ] as a substrate of amino acid transferase and glutamate dehydrogenase, and influences epigenetic regulation in ageing [ 7 , 19 , 20 ]and metabolism [ 8 , 49 ] as an obligate substrate of histone and DNA demethylases [ 15 , 50 ]. Exogenous AKG also affects the cellular energy supply under the effects of various adverse factors [ 14 , [51] , [52] , [53] ], such as bacterial endotoxins and hypoxia. AKG supplementation decreased the levels of ROS [ 7 ] and inflammatory cytokines in mice [ 19 ], lessening the adverse impact of ageing and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…AKG is an important intermediate in the TCA cycle, impacts ATP production as a key point in the anaplerotic pathway [ 7 , 15 , 46 , 47 ], involved in the biosynthesis of proteins and amino acids [ 48 ] as a substrate of amino acid transferase and glutamate dehydrogenase, and influences epigenetic regulation in ageing [ 7 , 19 , 20 ]and metabolism [ 8 , 49 ] as an obligate substrate of histone and DNA demethylases [ 15 , 50 ]. Exogenous AKG also affects the cellular energy supply under the effects of various adverse factors [ 14 , [51] , [52] , [53] ], such as bacterial endotoxins and hypoxia. AKG supplementation decreased the levels of ROS [ 7 ] and inflammatory cytokines in mice [ 19 ], lessening the adverse impact of ageing and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism may be due to the nonenzymatic oxidative decarboxylation in which ketone group in α -carbon atom is combined with H 2 O 2 to form corresponding carboxylic acid, CO 2 , and H 2 O. AKG serves as a key intermediate in the TCA cycle and participates in nonenzymatic oxidative decarboxylation in the H 2 O 2 decomposition. It has been demonstrated that AKG significantly elevated antioxidative capacity by decreasing the level of H 2 O 2 in the liver and intestinal mucosa of ducks [ 32 ]. Also, AKG performs a protective role in intestinal cells damage induced by H 2 O 2 through mitochondria pathway [ 33 ].…”
Section: Antioxidative Function Of Akgmentioning
confidence: 99%
“…Exogenous AKG has been reported to promote absorption of nutrients and even modulate intestinal amino acid metabolism and immunity (6,7). In recent years, the effects of AKG on intestinal energy status and anti-oxidative capacity have been studied in ducks (8), rats (9), fruit flies (10) and piglets (11). However, a handful of studies have been reported the clinical benefits of AKG in improving immunity in malnutrition or inflammatory diseases to maintain intestinal structure and function under stress (12,13).…”
Section: Introductionmentioning
confidence: 99%